The Identity problem with teenager: A dynamic approach through the Rorschach test for teens seeking psychological help - Hadj Mohamed, Saliha (Journal of Human Sciences, 2022)
The actual clinical study allowed the detection of the existence of an identity problem for adolescents who seek psychological help, through the application of the Rorschach test and the clinical interview; Based on analytical theory as a frame of reference. Depending on the analysis of adolescents responses on Rorschach panels, especially human answers and relationships, and determining their quality as an important indication of identity, in order to extract patterns indications of identity, and provide a clinical hint about adolescents identity. The results of the study concluded that adolescents were classified according to their type of identity into three categories: one with a relatively fixed identity; a group with a vibrating identity and a category with a fragile identity.